2020
DOI: 10.15407/ufm.21.04.580
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic αʺ-Fe16N2-Type Phase of Non-Stoichiometric Composition: Current Status of Research and Microscopic Statistical-Thermodynamic Model

Abstract: The literature (experimental and theoretical) data on the tetragonality of martensite with interstitial–substitutional alloying elements and vacancies are reviewed and analysed. Special attention is paid to the studying the martensitic αʺ-Fe16N2-type phase with unique and promising magnetic properties as an alternative to the rare-earth intermetallics or permendur on the world market of the production of permanent magnets. The period since its discovery to the current status of research is covered. A statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 99 publications
1
3
0
4
Order By: Relevance
“…У разі зміни зовнішніх термодинамічних умов (температури, тиску, магнетного поля) з'являється можливість реґулювати будову та тим самим властивості речовини даного тіла, а це означає, що одержується спосіб керування функціональністю матеріялу на його основі. Одну з таких можливостей розглянуто у даній роботі на прикладі одного з магнетних матеріялів сучасности [1][2][3][4]. Останні є складовими при використанні у магнетних пристроях, і певне вдосконалення таких матеріялів може мати значний вплив на енергетичні ресурси та сферу застосування.…”
Section: вступunclassified
See 2 more Smart Citations
“…У разі зміни зовнішніх термодинамічних умов (температури, тиску, магнетного поля) з'являється можливість реґулювати будову та тим самим властивості речовини даного тіла, а це означає, що одержується спосіб керування функціональністю матеріялу на його основі. Одну з таких можливостей розглянуто у даній роботі на прикладі одного з магнетних матеріялів сучасности [1][2][3][4]. Останні є складовими при використанні у магнетних пристроях, і певне вдосконалення таких матеріялів може мати значний вплив на енергетичні ресурси та сферу застосування.…”
Section: вступunclassified
“…Згідно з [14,15], припустімо, що атоми X по октаедричних міжвузловинах розподілені впорядковано за надструктурним типом фази α″-Fe16N2 [16,17] (про нинішній стан дос-ліджень цієї фази див. в огляді [3]). Тоді маємо [15]:…”
Section: «конфіґураційна» вільна енергія твердого розчину неметалічниunclassified
See 1 more Smart Citation
“…The development of surfacing technologies is carried out by taking into account theoretical approaches to the selection of the alloy component composition [22,23,24], technological heredity [25], and optimization of detail manufacturing technologies [26] to ensure the functioning of products during the life cycle [27,28].…”
Section: Introdactionmentioning
confidence: 99%
“…Permanent magnets for functional applications are currently based largely on the costly rare earths such as Sm, Nd, and Gd and there is great need to find new cost-effective alternatives. [1][2][3] In this connection, magnetic nitrides, such as the iron nitrides, appear to be promising, 4 and among these a 00 -Fe 16 N 2 , 5,6 discovered in 1951, 7 stands out because it supports a giant magnetization density. [8][9][10] Kim and Takayashi 8 have reported a magnetization of 2.58 T and Sugita et al reported an even higher magnetization of 2.8-3.0 T. 11 These large values of the magnetization are surprising because they exceed the maximum magnetization expected from the Slater-Pauling curve, 12 which attributes the magnetic saturation of an itinerant ferromagnet solely to the number of empty states in the 3d shell and this number is maximized for the FeCo alloys at a magnetization density of about 2.45 T. Giant magnetization in a 00 -Fe 16 N 2 thus implies the emergence of localized magnetic moments in the material.…”
Section: Introductionmentioning
confidence: 99%